FINE-GRAINED-RIM MINERALOGY OF THE COLD BOKKEVELD CM CHONDRITE - Zega T.J.; Buseck P.R. (My University, 2003)
A chrysotile-like phase, cronstedtite, polygonal serpentine, pentlandite, and finely intergrown tochilinite comprise the fine-grained rim (FGR) mineralogy of the Cold Bokkeveld CM chondrite. Transmission electron microscope images combined with compositional data indicate reaction among cronstedtite, the chrysotile-like phase, and polygonal serpentine. The Mg/(Mg+Fe) ratios of the cronstedtite are higher than those reported for the less altered Murchison CM chondrite. Cronstedtite grains exhibit layer separations, particularly at their boundaries.The FGRs surround different chondrule types but have similar bulk compositions and mineralogy. Ca is depleted in the FGRs relative to the bulk CM chondrite. The FGRs display non-uniform thicknesses, especially where they coat embayed chondrule areas, and they exhibit grain-size coarsening outward from the chondrules they enclose. FGR formation in Cold Bokkeveld is most plausibly explained by multiple accretionary episodes during which progressively coarser dust was deposited onto chondrules, presumably in the solar nebula. The compositional and mineralogic data are consistent with aqueous alteration on the parent body.